The design and application of an intensive care unit point-of-care nursing handover checklist based on the situation, background, assessment, and recommendation technique - Wang, Lei; Ma, Yu-Jie; Chen, Xiao-Ting; Zhang, Jie; Liu, Tao (Frontiers in Public Health, 2022)
Objective This study aims to analyze the effect of using an intensive care unit point-of-care nursing handover checklist based on the situation, background, assessment, and recommendation (SBAR) communication technique. Methods An intensive care unit point-of-care nursing handover checklist was designed based on the SBAR technique, and standard point-of-care nursing handover procedures and effect assessment indicators were established to compare the occurrence of adverse handover events and nursing risks with those previously observed. Results Before and after the application of the intensive care unit point-of-care SBAR checklist, the occurrence of missed items during the handover was 7.26 and 2.02%, inadequate preparation for handover was 28.33 and 5%, and nursing risks were 5 and 1.67%, respectively. Conclusion Based on the SBAR technique, the application of an intensive care unit point-of-care nursing checklist reduced the occurrence of adverse handover events and nursing risks.